Proliferation of Chondrodonta in upper Cenomanian shallow-water limestones of the Adriatic Carbonate Platform (Croatia) as a proxy of environmental instability. (June 2022) - Del Viscio, Gabriella; Morsilli, Michele; Posenato, Renato; Frijia, Gianluca; Moro, Alan; Mezga, Aleksandar
Abstract: The occurrence of the opportunistic, oyster-like bivalve Chondrodonta is widely documented in late Cenomanian shallow-water carbonates of the Tethyan Realm. Despite its high abundance and widespread geographic distribution, the precise relationship between the time of its proliferation and the environmental perturbations that precede the Cenomanian – Turonian anoxic event, has not been yet investigated. Stratigraphic and geochemical analyses of the upper Cenomanian Chondrodonta accumulations within the inner platform limestones of the Adriatic Carbonate Platform (AdCP) are performed to assess the timing and the environmental controls on the Chondrodonta proliferation. In the study area, Chondrodonta appears as sparse to common individuals within radiolitid rudist beds and reaches a phase of proliferation and predominance in the benthic community. This biotic event has been correlated via C- and Sr-isotopes to a late Cenomanian environmental stress phase, occurred in shallow-water settings and in the deep counterparts. This environmental stress phase on the AdCP was characterized by high nutrient levels, fluctuating seawater oxygenation, and more terrigenous inputs that favored the flourishment of Chondrodonta and its transient predominance over the less resilient rudists. This bioevent seems to be recurrent at the central Tethys scale, allowing to consider the proliferation of Chondrodonta in shallow-water carbonate platforms as a stratigraphic marker for a late Cenomanian environmental stress phase preceding the anoxic event. Highlights: Chondrodonta flourishes at expenses of rudists on the Adriatic Carbonate Platform. Chondrodonta spreads in the late Cenomanian, before the onset of the OAE2. Higher nutrients and fluctuating seawater parameters favour its thriving. Chondrodonta beds correlate to environmental stress in nearby basin counterparts. Chondrodonta proliferation as biomarker of a late Cenomanian ecological stress phase.